Optimasi Jaringan HSDPA di Wilayah Kota Malang Menggunakan Drive Test - Agnes Estuning Tyas (Politeknik Negeri Malang, 2016)
With the influence of customer growth and environmental influences from an HSDPA network in the form of nodeB which stands in the Malang City area, it can experience integration. This causes measurements to be carried out continuously and periodically to provide the latest radio environmental information. The vendor as the network operator performs optimization in order to provide customers with the best quality service. One of them is in the form of network performance which aims to ensure that network resources are used efficiently. The method in achieving network optimization that is still used by vendors in Indonesia is by measuring network performance, then analyzing the results of measuring network performance and finally network tuning. For measuring network performance using a test drive. Of the 13 nodeB in Lowokwaru District, Malang City, it is necessary to optimize the HSDPA network with the suggestion of a downtilt antenna on the Ketawanggede nodeB sector 3, which is 2º The results of the calculation of the path loss parameters from each of the 13 nodeBs obtained the highest value of 125.31 dB at nodeB Ketawanggede and the lowest 114.29 dB at nodeB Vinolia Malang sector 3. The results of the RSCP parameter calculation at 13 nodeB obtained the best value at nodeB Vinolia Malang sector 3 with RSCP of -69.29dBm. While the worst value at nodeB Ketawanggede with RSCP is -80.31dBm.